PENGARUH SDM, KOMITMEN, MOTIVASI TERHADAP KINERJA DOSEN DAN REWARD SEBAGAI V ARIABEL MODERATING (Studi Pada Universitas Lakidende Unaaha) - Ilham (FEB Universitas Lakidende, 2019)
This study aims to examine the effect of human resources, commitment and motivation on lecturer performance and examine the effect of rewards on the relationship between HR, commitment and motivation with lecturer performance. The sample of this study were (Permanent Lecturers and Civil Servants Foundation Lecturers) who conducted learning, research and community service at Lakidende Unaaha University with a total of 50 lecturers. Data were collected using a questionnaire, of the 50 questionnaires distributed, returned 50 questionnaires and which could be evaluated as many as 50 questionnaires by path analysis of the SmartPLS 2.0 M3 software. The results of this study concluded that Motivation influences Lecturer Performance, and Reward if placed as an independent variable also has a significant effect on Lecturer Performance, and HR, commitment has a significant effect on lecturer performance. simultaneously human resources, commitment, motivation and reward have a significant effect on lecturer performance and reward influences the relationship between HR, Commitment and Motivation on Lecturer Performance and reward is a moderating variable